DEVELOPMENT OF INDUSTRIAL ENTERPRISES AND ANALYSIS OF THE FACTORS OF THEIR COMPETITIVENESS - Uktamov Khusniddin (Scholar Express Journals, 2024)
In this article, the concept of forming the competitiveness of small business entities and its essence and the concept of Competitiveness are discussed about such aspects as competitive advantage, price competition, strategic management and other historical and sociocultural aspects, and Competitiveness is also an independent variable, an intermediate variable or a complete variable depending on the approach in research. considered as a dependent variable, consisting of different dissimilar factors depending on the field of activity, and the competitiveness of small and medium-sized hotels in the hotel sector compared to their competitors in terms of price, service quality, gross profit, planning and achieving business goals.
Keywords: Small Business; Product; Firm